The emergence of drug resistance to targeted cancer therapies: Clinical evidence. (December 2019) - Sarmento-Ribeiro, Ana Bela; Scorilas, Andreas; Gonçalves, Ana Cristina; Efferth, Thomas; Trougakos, Ioannis P.
Abstract: For many decades classical anti-tumor therapies included chemotherapy, radiation and surgery; however, in the last two decades, following the identification of the genomic drivers and main hallmarks of cancer, the introduction of therapies that target specific tumor-promoting oncogenic or non-oncogenic pathways, has revolutionized cancer therapeutics. Despite the significant progress in cancer therapy, clinical oncologists are often facing the primary impediment of anticancer drug resistance, as many cancer patients display either intrinsic chemoresistance from the very beginning of the therapy or after initial responses and upon repeated drug treatment cycles, acquired drug resistance develops and thus relapse emerges, resulting in increased mortality. Our attempts to understand the molecular basis underlying these drug resistance phenotypes in pre-clinical models and patient specimens revealed the extreme plasticity and adaptive pathways employed by tumor cells, being under sustained stress and extensive genomic/proteomic instability due to the applied therapeutic regimens. Subsequent efforts have yielded more effective inhibitors and combinatorial approaches (e.g. the use of specific pharmacologic inhibitors with immunotherapy) that exhibit synergistic effects against tumor cells, hence enhancing therapeutic indices. Furthermore, new advanced methodologies that allow for the early detection of genetic/epigenetic alterations that lead to drug chemoresistance and prospective validation of biomarkers which identify patients that will beneﬁt from certain drug classes, have started to improve the clinical outcome. This review discusses emerging principles of drug resistance to cancer therapies targeting a wide array of oncogenic kinases, along with hedgehog pathway and the proteasome and apoptotic inducers, as well as epigenetic and metabolic modulators. We further discuss mechanisms of resistance to monoclonal antibodies, immunomodulators and immune checkpoint inhibitors, potential biomarkers of drug response/drug resistance, along with possible new therapeutic avenues for the clinicians to combat devastating drug resistant malignancies. It is foreseen that these topics will be major areas of focused multidisciplinary translational research in the years to come.